Pengaruh Green Marketing dan Service Quality terhadap Loyalitas Pelanggan dengan Customer Satisfaction sebagai Variabel Intervening (Studi Kasus di Starbucks Coffee Kota Surabaya) - Rizqiningsih, Dwitriana Ulfi; Widodo, Arry (Jurnal Samudra Ekonomi dan Bisnis, 2021)
This study aims to determine the effect of green marketing and service quality on customer loyalty through customer satisfaction as an intervening variable. In the analysis process, this research applies a case study on Starbucks Coffee as a business that implements a green marketing strategy. The method used is a quantitative paradigm with descriptive and causal research types, as well as the SEM-PLS analysis method. Non-probability sampling technique was used to select a sample of 385 Starbucks Coffee customers in Surabaya City. Based on the results, it was concluded that green marketing and service quality had a positive and significant effect on customer loyalty either directly or through customer satisfaction as an intervening variable.